Effects of conservation agriculture practices on productivity and nutrient uptake in rice-wheat cropping system - kumar, Pardeep; Kumar, Satish; Jat, M.L.; Yadav, Ashok; Dhaka, A.K. (Annals of Agricultural Research, 2018)
A field experiment was conducted at the participatory strategic research and learning platform forclimate smart agriculture at Taraori, Karnal, Haryana during Kharif, and rabi seasons of 2013-14and 2014-15 in collaboration with CIMMYT under CGIAR's research program on climate change,agriculture and food security (CIMMYT-CCAFS). Treatments were laid out in split plot factorialdesign having twelve treatment combinations for each crop with three replications.The treatmentconsisted of four tillage and crop establishment (TCE) methods in main plots and four treatments insubplot of rice cultivar and nitrogen management under rice-wheat cropping system. Our resultsshows that TCE methods failed to produce any significant variation on grain yield, straw yield,biological yield, harvest index and wheat equivalent yield of rice during both the years. The highestgrain yield (7.15 t/ha), biological yield (15.73 t/ha) and harvest index (45.51%) were recorded underthe hybrid plot during 2014.In both the years higher grain yield was observed under hybrid ricecultivars than Basmati rice cultivars.The hybrid rice resulted into 24.8 and 25.8% higher total N,23.4 and 25.6% higher total P and 13.3 and 10.8% higher K uptake over basmati rice during 2013-14and 2014-15, respectively.The wheat sown under ZT direct seeded rice -ZT wheat with full retained(ZT DSR- ZT W + R) resulted 8.63% (2013-14) and 14.60% (2014-15) higher grain yield comparedpuddled transplanted rice followed by conventional tilled wheat (PTR-CTW). Wheat grown underZT DSR-ZTW with and without residue resulted into significantly higher total NPK uptake duringboth cropping years.